Rhabdomyolysis following Acute Extended-Release Quetiapine Poisoning: A Case Report - Liolios, Antonios; Sentissi, Othman (Case Reports in Psychiatry, 2012)
Background. During the past few years, there have been a number of case reports concerning rhabdomyolysis following quetiapine poisoning; however, there has been none concerning the medication in its extended-release form. Methods. We present the case report of a 48-year-old man presenting a major depressive disorder and borderline personality disorder, who after voluntary intoxication with 12000 mg of quetiapine extended-release developed signs of acute rhabdomyolysis. Results. The rhabdomyolysis was confirmed by the laboratory and the clinical findings, with elevated levels of creatinine, creatine phosphokinase, and CRP. Discussion. We would like to pinpoint the importance of this complication and our concern of prescribing it for psychiatric patients with chronic somatic comorbidities.